A COOPERATIVE PRINCIPLE APPROACH ON THE DIALOGUES OF RCTI’S OFFICE BOY - Rangga Wisnu Novika (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2008)
Office Boy is a situational comedy aired by one of the Indonesian private television station. It is always about the daily life of an HR department in which office boy is a part. The joke creation in the program is unique. It is, then, a reason to explore the dialogues in the episodes by viewing the interactive communication between the characters through a pragmatic approach, particularly the cooperative principles proposed by Grice.